Lexical Metaphor Use in Advertising Slogans: A Systemic Functional Perspective - Annisa Atthormizi; Duaa Salameh (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to analyze the types and meanings of lexical metaphors used in selected educational slogan advertisements, with a particular focus on how metaphorical expressions contribute to persuasive meaning within promotional language. Methodology: This research employed a descriptive qualitative design using textual and pictorial analysis. The data were limited to slogan advertisements from three educational institutions The Doon World School, The Asian School Dehradun, and Junior High School Maria Mediatrix collected through documentation. The analysis was conducted using Halliday’s Systemic Functional Linguistics (SFL) framework, Saragih’s lexical metaphor classification, and Royce’s verbo-pictorial theory. Main Findings: The findings indicate that the slogans predominantly employ noun–noun and noun–verb lexical metaphors. These metaphors function to reinforce intended meanings and enhance slogan attractiveness and clarity. The analysis also shows a close relationship between literal and metaphorical meanings, suggesting that conventional metaphors are more frequently used than novel ones within the analyzed data set. Novelty/Originality of this study: This study offers an integrative analysis combining Saragih’s lexical metaphor typology and Halliday’s SFL approach within the specific and limited context of educational slogan advertisements. While the findings cannot be generalized beyond the selected data, the study contributes to a focused understanding of how lexical metaphors function as persuasive linguistic resources in educational advertising discourse.